SEVERE DISEASE DEVELOPMENT PREDICTION DEVICE, SEVERE DISEASE DEVELOPMENT PREDICTION METHOD, AND PROGRAM - MITSUKURA Yasue; ISHII Makoto; FUKUNAGA Koichi; TERAI Hideki (2023)
Through the present invention, prediction relating to development of severe disease in a virus-infected person is performed by a simpler method.　A severe disease development prediction device 20 comprises a feature value extraction unit 212, a prediction model construction unit 213, and a prediction execution unit 214. The feature value extraction unit 212 extracts, as feature values, a test value for each of a plurality of components included in blood of a virus-infected person. The prediction model construction unit 213 performs logistics regression analysis using as factors the feature values extracted from the blood of the subject infected person, and using as the objective variable whether or not the subject infected person developed severe disease as a result of infection with the virus, and thereby constructs a prediction model for making a prediction relating to development of severe disease. The prediction execution unit 214 makes a prediction relating to development of severe disease in a prediction-subject infected person on the basis of the prediction model and feature values extracted from the blood of the prediction-subject infected person. Grâce à la présente invention, la prédiction relative au développement d'une maladie grave chez une personne infectée par un virus est effectuée par un procédé plus simple.　Un dispositif de prédiction de développement d'une maladie grave 20 comprend une unité d'extraction de valeurs caractéristiques 212, une unité de construction de modèle de prédiction 213 et une unité d'exécution de prédiction 214. L'unité d'extraction de valeurs caractéristiques 212 extrait, en tant que valeurs caractéristiques, une valeur de test pour chacun d'une pluralité de composants compris dans le sang d'une personne infectée par un virus. L'unité de construction de modèle de prédiction 213 réalise une analyse de régression logistique en utilisant comme facteurs les valeurs caractéristiques extraites du sang de la personne infectée sujet, et en utilisant en tant que variable objective le fait que la personne infectée sujet ait ou non développé une maladie grave suite à une infection par le virus, et construit ainsi un modèle de prédiction pour la réalisation d'une prédiction relative au développement d'une maladie grave. L'unité d'exécution de prédiction 214 effectue une prédiction relative au développement d'une maladie grave chez une personne infectée sujet de prédiction sur la base du modèle de prédiction et des valeurs caractéristiques extraites du sang de la personne infectée sujet de prédiction. より簡便な方法で、ウイルスの感染者の重症化に関する予測を行う。　重症化予測装置２０は、特徴量抽出部２１２と、予測モデル構築部２１３と、予測実行部２１４と、を備える。特徴量抽出部２１２は、ウイルスの感染者の血液に含まれる複数の成分それぞれの検査値を特徴量として抽出する。予測モデル構築部２１３は、被験者となる感染者の血液から抽出された特徴量を因子とすると共に、被験者となる感染者がウイルスへの感染により重症化したか否かを目的変数として、ロジスティックス回 帰分析を行うことにより、重症化に関する予測をする予測モデルを構築する。予測実行部２１４は、予測対象者となる感染者の血液から抽出された特徴量と、予測モデルとに基づいて、予測対象者となる感染者の重症化に関する予測をする。